Pemetaan Upaya Preventif Retensi Personel Rangka Pengendalian Kasus Pemberhentian Tidak Dengan Hormat (PTDH) pada Kepolisian Republik Indonesia - Muhammad Aprisakundi; Retno Kusumastuti (Jurnal Manajemen dan Organisasi, 2022)
This study is important to be carried out in the context of the Indonesian National Police (POLRI). This study analysis the mapping of preventive employee retention efforts that have been carried out by the Indonesian National Police in tackling PTDH. This research uses a post-positivist research paradigm. Data were collected using in-depth interviews and a literature study. The results of the study are, first, preventive efforts, namely the superiors to always check the condition of members from the physical, daily to the psychological side of members. Second, repressive efforts, namely by giving punishments that can deter violators and increase supervision of members. Third, a solution effort is to look for reasons why members do a dissertion and find relevant solution. Based on the results, the efforts of POLRI employee retention in tackling PTDH are considered not optimal, so innovation is needed. One of them is by providing the official home infrastructure with the smart home concept. The implications of this research are expected to provide improvements in terms of existing retention management so as to increase the retention of POLRI membership.